El proceso de canonización - Royo Mejía, Alberto (Revista española de derecho canónico, 2013)
The author discusses in this article some current issues about the causes of saints, in light of the upcominng canonization of Popes John Paul II and John XXIII. The particularity of this ceremony gives rise to the issue of the current brevity of these causes compared with earlier times, reviewing the legislative changes these procedures have undergone since Vatican II. Furthermore the author discusses, the characteristics of the candidate to the altar that, according to the canonical tradition, should be taken into account in the necessary discernment, either by the bishop of the diocese or by those who want to be promoters of a cause, when beginning to take the steps that will lead to the instrucction of the procedure